The Urgency of Special Protection for Children Post Disaster - Titie Yustisia Lestari; Ridwan Tahir; Andi Afdhalia Sri Hayati (Criminal of Law Department, Faculty of Law, Pattimura University, 2022)
Children's rights should be treated differently from adults, especially in vulnerable situations such as after a disaster. In some cases, the fulfillment of children's rights is often neglected due to the chaotic situation because the parties involved are still busy revitalizing the affected areas and meeting the needs of other vulnerable groups. This study is a normative study by examining children's rights after the disaster in several international and national regulations. The study results show that both the Convention on the Rights of the Child and Law Number 35 of 2014, which has been amended by Law Number 23 of 2002, clearly state the protection of children, including in the event of a disaster. However, the Disaster Management Law not detail the protection and fulfillment of children's rights specifically and still places children as beneficiaries, not as actors whose aspirations must be heard.